2020
DOI: 10.1002/sctm.19-0433
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar wars: The rise of in vitro models to understand human lung alveolar maintenance, regeneration, and disease

Abstract: Diseases such as idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, and bronchopulmonary dysplasia injure the gas‐exchanging alveoli of the human lung. Animal studies have indicated that dysregulation of alveolar cells, including alveolar type II stem/progenitor cells, is implicated in disease pathogenesis. Due to mouse‐human differences, there has been a desperate need to develop human‐relevant lung models that can more closely recapitulate the human lung during homeostasis, injury repair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 130 publications
(165 reference statements)
0
63
0
Order By: Relevance
“…The presence and/or roles of facultative progenitors in human lung is unknown. Human AT2 cells can be differentiated into AT1 cells but cultures are short-lived, neither demonstrating long-term self-renewal nor enabling expansion for disease modeling 4,10,11 , while requirements for feeder cells impede definition of specific niche components 12,13 . Here, we established long-term organoid culture of distal human lung, including AT2 and basal stem cells, which was applied to functional progenitor validation and SARS-CoV-2 modeling.…”
mentioning
confidence: 99%
“…The presence and/or roles of facultative progenitors in human lung is unknown. Human AT2 cells can be differentiated into AT1 cells but cultures are short-lived, neither demonstrating long-term self-renewal nor enabling expansion for disease modeling 4,10,11 , while requirements for feeder cells impede definition of specific niche components 12,13 . Here, we established long-term organoid culture of distal human lung, including AT2 and basal stem cells, which was applied to functional progenitor validation and SARS-CoV-2 modeling.…”
mentioning
confidence: 99%
“…Our studies on synthetic lipophilic carriers ( Incani et al, 2010 ) showed that these two domains could be engineered to obtain effective siRNA delivery agents to a variety of cells. It may be possible to set-up ECM mimics of pulmonary tissue ( Evans and Lee, 2020 ) to better understand the mediators of siRNA delivery into the cells, given the implication of this process on the potency of siRNAs agents for anti-viral activity.…”
Section: Experience With Rnai Therapy Of Sars-cov-2mentioning
confidence: 99%
“…There is strong need to understand the mechanisms of alveolar maintenance and repair because damage to this region underlies many chronic adult lung diseases, such as chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, acute respiratory failure in pneumonia, and acute respiratory distress syndrome. Additionally, insufficient development of alveoli results in various neonatal and childhood diseases including bronchopulmonary dysplasia [1]. Despite the pivotal role of the alveoli in the development of lung diseases, the pathogenesis of these various conditions is still largely unknown, and treatment options for patients remain limited.…”
Section: Lung Chronic Diseases: a Brief Overviewmentioning
confidence: 99%